SINO-US COMPETITION DYNAMICS IN SOUTHEAST ASIA: A CASE STUDY OF THE BELT AND ROAD INITIATIVE AND FREE AND OPEN INDO-PACIFIC - Falevi, Muhammad Reza; Julian Aldrin Pasha (Politik Indonesia: Indonesian Political Science Review, 2024)
This study examines the competitive dynamics in Southeast Asia under the frameworks of the Belt and Road Initiative (BRI) and the Free and Open Indo-Pacific (FOIP), two key strategies reshaping the region’s geopolitical and economic landscape. Using a qualitative approach supported by extensive literature review, the research applies Kenneth Waltz's Power Balance Theory to analyze this rivalry. The BRI has accelerated infrastructure development and regional connectivity, strengthening economic ties between China and Southeast Asian nations. However, it raises concerns over economic dependence and the potential for China to exert undue political influence. On the other hand, the FOIP seeks to counterbalance China’s influence by enhancing alliances and security partnerships led by the United States and its allies. This rivalry creates a complex scenario for Southeast Asian countries, requiring them to navigate economic opportunities while addressing geopolitical risks. The study highlights how these initiatives influence foreign policy strategies across the region and their broader implications for stability and security. By exploring the interplay of economic and strategic factors, the research deepens understanding of Southeast Asia’s evolving power dynamics and provides insights into managing the challenges posed by these competing frameworks. This analysis enriches the discourse on the region’s critical role in a contested global order.